Eco-friendly laminated strand lumber from date palm rachis : analysis of mechanical properties by Taguchi design of experiment = Ekološki prihvatljiva uslojena drvonitna građa od lisnih osi palme datulje : analiza mehaničkih svojstava Taguchi metodom pripreme istraživanja - Shafie, Masoud (Array, 2019)
This study was performed to use date palm rachis, as a low value bio-waste, in the manufacture of a high value added eco-friendly structural composite lumber. Taguchi design of experiments was applied to analyse the effect of raw material and product parameters on the mechanical properties of laminated strand lumber from date palm rachis. The results indicate that the composite exhibits similar or superior strength properties compared to solid lumber and engineered products from wood or other lignocellulosic material for building sector. Taguchi design of experiments was assessed as a powerful and cost effective technique to obtain optimal levels for maximizing the mechanical properties of the environmentally-friendly composite. Maximum values for the mechanical properties of date palm rachis-based LSL were obtained from a combination of 20 mm product thickness, 10 % resin content, 4mm strand thickness, and 850 kg/m3 product density. Product thickness with an 81.3 % contribution and strand thickness with an 80 % contribution have the highest effects on the flatwise stiffness and compression strength perpendicular to grain, respectively.